1996
DOI: 10.1111/j.1525-1470.1996.tb01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma in a Girl after Cobalt Irradiation to the Cranium for Acute Lymphoblastic Leukemia: Case Report and Literature Review

Abstract: A 12-year-old girl had a lesion located on the upper part of the scalp that was clinically interpreted as a melanocytic nevus and corresponded histologically to a basal cell carcinoma. At age 2 years she had been diagnosed as having acute lymphoblastic leukemia L1, for which she was treated with systemic chemotherapy. She also received telecobalt therapy to the whole cranium for prophylaxis of meningeal leukosis. Having rejected other possible causes that can favor the appearance of basal cell carcinoma during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…Cases of BCC in the pediatric population have been reported in association with basal cell nevus syndrome, 1 xeroderma pigmentosum, 2 and nevus sebaceus 3 and after highdose radiotherapy. 4 Isolated cases of BCC unrelated to one of these causes are seldom reported in pediatric patients. Consequently, clinicians often have a low index of suspicion, leading to delay in diagnosis.…”
mentioning
confidence: 99%
“…Cases of BCC in the pediatric population have been reported in association with basal cell nevus syndrome, 1 xeroderma pigmentosum, 2 and nevus sebaceus 3 and after highdose radiotherapy. 4 Isolated cases of BCC unrelated to one of these causes are seldom reported in pediatric patients. Consequently, clinicians often have a low index of suspicion, leading to delay in diagnosis.…”
mentioning
confidence: 99%
“…In Table 1, the characteristics of BCC in survivors of childhood cancer are summarized. BCC after radiation therapy has also been reported in case reports (2)(3)(4). BCC has been reported to be associated with underlying conditions such as basal cell nevus syndrome, albinism, and xeroderma pigmentosum; burn scars; and radiation therapy (9).…”
Section: Discussionmentioning
confidence: 95%
“…Lichter et al [11] reported a higher incidence of BCC and SCC when radiation therapy was performed under age 20. An increased risk of BCC in areas of previous irradiation, especially on the scalp where they are hidden from view is noted in the literature and should be paid close attention to by physicians examining this at-risk population [10][11][12]. As skin cancer is easily treated when detected at an early stage, the increased incidence of skin cancer in adult survivors of childhood cancer demonstrates the need for regular and routine skin screening to ensure early detection and management [4,10].…”
Section: Discussionmentioning
confidence: 99%